Baha'u'll'ah and the new era : an introduction to the Bahai faith - Esslemont, John Ebenezer (Baha' 'ai Publishing Trust, 1970)
The book explains in depth the teachings, history and practices of the Baha'i faith. It is one of the world's fastest growing religions and it teaches about how to use spiritual principles to achieve personal growth, loving families and united supportive communities. It introduces to a community that is committed to sustaining and nurturing a loving vibrant spiritual life for families.